Strategi Pengelolaan Relasi Pelanggan dan Kualitas Layanan dalam Meningkatkan Kepuasan Pelanggan Menggunakan Analisis SWOT pada PT Holistik Homecare di Ciputat Tangerang Selatan - Teza Bany Safa; Munarsih Munarsih (Excellent, 2025)
This study aims to analyze customer relationship management strategies and service quality in improving customer satisfaction at PT Holistik Homecare in Ciputat, South Tangerang, using the SWOT analysis method. The research focuses on identifying internal factors (strengths and weaknesses), external factors (opportunities and threats), and formulating strategies that can be applied by the company to maintain and enhance customer satisfaction. The research method used is descriptive qualitative, with data collected through in-depth interviews with management, medical staff, and customers of PT Holistik Homecare, supported by secondary company data. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with validation using triangulation techniques. The results indicate that the company’s main strengths lie in the quality of medical services, the availability of complete medical equipment, and flexible payment systems. Weaknesses include limited service personnel. Opportunities involve the increasing demand for homecare services and advancements in health technology, while the main threats come from competitors offering similar services. Recommended strategies include increasing the number of service personnel, optimizing communication and service personalization, and developing technology-based innovations.